Outcomes of 25-Gauge Vitrectomy for Tractional and Nontractional Diabetic Macular Edema with Proliferative Diabetic Retinopathy. (11th December 2019) - Someya, Hideaki; Takayama, Kei; Takeuchi, Masaru; Yokoyama, Hiroshi; Kimura, Takeshi; Morioka, Masakazu; Takamura, Yoshihiro; Sameshima, Seiji; Ueda, Tetsuo; Ogata, Nahoko; Tashiro, Maki; Kitano, Shigehiko; et al.
Abstract : The benefit of pars plana vitrectomy with internal limiting membrane peeling for tractional macular edema and diffuse nontractional macular edema in diabetic retinopathy has been reported. Although these studies had included various stages, use of conventional 20-gauge vitrectomy system, small number of cases, single-center study, and lack of retinal structure measurements were limitations. We compared one-year outcomes of 25-gauge vitrectomy for refractory diabetic macular edema with or without the tractional proliferative membrane in proliferative diabetic retinopathy (PDR) eyes and examined the prognostic factors for postoperative visual acuity. A total of consecutive 116 PDR eyes of 116 patients that underwent 25-gauge vitrectomy for tractional macular edema (TME group: 56 eyes) or nontractional macular edema (nTME group: 60 eyes) at six centers were retrospectively reviewed. Visual acuity (VA), central macular thickness (CMT), complications, and postoperative treatments before and 12 months after vitrectomy were compared. Mean VA improved significantly in each group (both P < 0.01 ), and mean CMT decreased significantly in each group (both P < 0.01 ). Thirteen eyes underwent additional vitrectomy, six eyes developed neovascular glaucoma, six eyes received intravitreal anti-VEGF injection, and thirteen eyes received subtenon triamcinolone acetonide injection. Multiple linear regression analysis showed that baseline VA and CMT in the TME group and kidney function in the nTME group were the predictable factors of the 12-month postoperative VA. Twenty-five-gauge vitrectomy effectively improved VA and macular structure both in TME and nTME groups. Baseline VA, CMT, and kidney function are important factors affecting postoperative VA.